PENERAPAN TEKNOLOGI INFORMASI DIGITAL LIBRARY UR DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL DI FISIP UNIVERSITAS RIAU - Rahmad Rival Hariyadi; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The number of innovations created to meet the needs that exist at this time requires the world of education, especially educational institutions ie universities to take part in innovating in order to meet the needs of students in berkegiatan. Forms of innovation created one of them is an online-based library that can be accessed anywhere, anytime and no time limit. The online library offers many useful features and functions within it. Viewed from the good innovation is that many educational institutions, especially universities in Indonesia to implement and also take advantage of online library. One of the universities in Indonesia that implement this online library is the University of Riau, Riau University has an online library that is a digital library UR. Implementation of an innovation made of course has a good influence, the research undertaken aims to examine the influence between technology acceptance model variables in UR digital library.The study involved 158 respondents from UR digital library users in FISIP University of Riau. How to determine the number of samples in this study using unknown population caused by the lack of definitive data about the number of users of UR digital library. Methods of data collection using questionnaires. Data were analyzed using Sructural Equation Model (SEM) with AMOS software program and SPSS. The research model uses Technology Acceptance Model (TAM) with perceived ease of use, perceived usefulness, attitude towards using and acceptance tested simultaneously.Data from the results of this study indicate ease perception variables have a significant value of influence that is t-Value or C.R of 2.508 to variable user attitudes and the total effect of 0.463. Usability perception variable has significant influence value that is t-Value or C.R 2,090 to user attitude variable and total influence 0,399. Usability perception variable has significant influence value that is t-Value or C.R equal to 1,968 to variable of acceptance and total influence equal to 0,362. User attitude variable has significant influence value that is t-Value or CR of 2555 to the variable of acceptance and the total influence of 0,503, and the perception of ease variable have insignificant influence value that is t-Value or CR equal to 0.448 to the variable of acceptance and total influence equal to 0.318.Keywords: Digital Library UR, Structural Equation Model (SEM), Technology Acceptance Model (TAM)